Arsitektur Data Pada PT. X - Gandawidjaja, Agustinus; Dewi, Lily Puspa; Handojo, Andreas (Jurnal Infra, 2015)
PT. X is a private company that commercially operated since 1991. It becomes the first company which produces Sodium Tripolyphosphate (STPP) in Indonesia. In order to support the business processing, PT. X only have a program holds its warehouse and also the general ledger. The program is lack of information system which is not whole integrated.For this reason, in this thesis, the analysis and design of architecture data information system is made for the company. The process begins by analyzing the business model and business strategy. After that, analysis the information technology in this company recently, then understanding the problem and looking at the need of information technology in the future. Next, making the design of architecture data which is suitable with business strategy and companys business process.